An empirical analysis of the productivity of Sarawak's manufacturing sector - Then, Catherine Fui Yean. (Universiti Malaysia Sarawak (UNIMAS), 2004)
This research paper is an empirical study on the productivity of the manufacturing sector in Sarawak. The manufacturing sector is an important source of Sarawakʼs revenue. The study proved that Sarawak had an input-driven economy in the nineteen eighties and the nineteen nineties as labour and capital productivity were important sources of productivity.